Communication Strategy of Tax Officersin Increasing Tax Compliance of Food and Beverage PBJT Taxpayers in Pondokgede District - Diana, Winna Wira; Supriyatno, Budi; Hakim, Azis (Dinasti Publisher, 2025)
This study aims to analyze the communication strategies used by tax officials to improve taxpayer compliance with the Certain Goods and Services Tax (PBJT) in the food and beverage sector in Pondok Gede District, Bekasi City. This study is driven by low tax compliance, despite the culinary sector's significant potential for Regional Original Revenue (PAD). The methodology employed in this study is qualitative with an interpretive approach, including in-depth interviews with the Head of the Tax and Retribution Unit (UPTD) in the Pondokgede area and several taxpayers. The analysis utilizes Cutlip, Center, and Broom's (2016) public communication strategy theory, which emphasizes the importance of strategic communication planning in fostering reciprocal relationships between public organizations and the public. Furthermore, this study relies on public service theory, which emphasizes empathetic communication and transparency as essential elements in public services focused on public satisfaction. The results of this study indicate that communication strategies play a central role in fostering awareness and trust among taxpayers. Three main approaches were used: a humanistic-interpersonal approach that emphasizes empathy and direct communication; a participatory approach that involves taxpayers in outreach activities; and a digital-adaptive approach through the use of social media and online platforms. The conclusion of this study indicates that improving tax compliance depends not only on fiscal policies or sanctions, but also on the quality of public communication that is educational, persuasive, and sustainable. Clear, open, and empathetic communication can build trust and motivate the public to actively participate in paying taxes as a contribution to regional development.